Design of 10 to 12 GHz Low Noise Amplifier for Ultrawideband (UWB) Syste - Toulali Islam; Lahbib Zenkouar (Institute of Advanced Engineering and Science, 2018)
Balanced amplifier is the structure proposed in this article, it provides better performance. In fact, the single amplifier meets the specification for noise figure and gain but fails to meet the return loss specification due to the large mis-matches on the input & outputs. To overcome this problem one solution is to use balanced amplifier topography. In this paper, a wide-band and highgain microwave balanced amplifier constituted with branch line coupler circuit is proposed. The amplifier is unconditionally stable in the band [9-13] GHz where the gain is about 20dB. The input reflection (S11) and output return loss (S22) at 11 GHz are -33.4dB and -33.5dB respectively.